2023
DOI: 10.1002/slct.202300185
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of TiO2 Nanoparticles in a Deep Eutectic Solvent for High‐Performance Photocatalysis: The Role of the Cosolvent

Abstract: Herein, we report a unique surfactant‐free synthetic pathway for the synthesis of anatase TiO2 catalysts in the size range of 13 to 20 nm by solvothermal method using choline chloride‐urea deep eutectic solvent (DES) as green media and 2‐propanol as cosolvent. The composition of reline was tuned by adding 0 (pure reline), 5, 10, 20 and 50 wt% of 2‐propanol. The amount of cosolvent was found to have a significant influence on TiO2 particle size, N2 isotherms and the magnitude of Urbach energy formed within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Additionally, it was shown that lowering pressure can reduce the kinetic energy of sputtered metal atoms, restricting their lateral movement at the liquid surface . On the other hand, lowering pressure can decrease the viscosity of the DES due to enhanced viscous dissipation and expansion of the hydrogen bonding network within the ChCl–urea components of DES . Such viscosity changes at the DES surface can influence long-range van der Waals interactions between DES and metallic NPs, impacting subsequent self-assembly of Ag NPs. , Consequently, deposition at higher pressures (Ag–P1, Ag–P2) may cause Ag atoms to diffuse partially into the bulk DES, promoting self-assembly into agglomerated particles.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was shown that lowering pressure can reduce the kinetic energy of sputtered metal atoms, restricting their lateral movement at the liquid surface . On the other hand, lowering pressure can decrease the viscosity of the DES due to enhanced viscous dissipation and expansion of the hydrogen bonding network within the ChCl–urea components of DES . Such viscosity changes at the DES surface can influence long-range van der Waals interactions between DES and metallic NPs, impacting subsequent self-assembly of Ag NPs. , Consequently, deposition at higher pressures (Ag–P1, Ag–P2) may cause Ag atoms to diffuse partially into the bulk DES, promoting self-assembly into agglomerated particles.…”
Section: Resultsmentioning
confidence: 99%